Two birds with one stone: Greening the EU's post-coronavirus recovery. Issue 2 (October 2020) - Palacková, Eva
If there is a silver lining to the ongoing pandemic, it could be its potential to change people's behaviour and policymakers' attitudes in favour of more sustainable models. The article focuses on the global struggle with the coronavirus and the resulting economic crisis, amid the ongoing crises of climate change and environmental degradation, and argues that returning to business as usual is not an option. Instead, it suggests learning from the experience, harnessing the momentum and embracing new ways of doing things to achieve green growth. The EU's post-coronavirus recovery package has this sort of transformative potential for the economies and societies of the member states. If it is implemented well, it could turn the crisis into an opportunity, and people will reap its benefits for generations to come.